Necesidad de reformar el artículo 236 del código civil ecuatoriano, correspondiente al tiempo de impugnar la paternidad por parte del marido, en aquellos hijos concebidos dentro del matrimonio, para que el padre pueda pedir la reclamación de la paternidad en cualquier tiempo que lo considere necesario, si existe causa legal que justifique su pedido - Paute Ramírez, Karina Elizabeth (2016)
The challenge is the procedure carried out by a person through judicial means permitted by law, in order that the decision or judgment repairing damage or performance of an obligation pursued. The challenge of parenthood is the fact by which the father is not considered father legitimated the son of her partner asks the competent authority to ignore the fact parenthood to which the alleged mother of his child attribute responsibility. The investigation of paternity in the legal field is expressly related to the examination of deoxyribonucleic acid, with the aim of pinpointing the true biological offspring of the child and thus be able to perform the corresponding procedure for contesting paternity and the child may thus have a fair IDENTITY. The Civil Code considers that the claim by the husband against the paternity of the child conceived by his wife during marriage must be made within sixty days from one who had knowledge of the delivery, this is irrelevant, because with the advancement of science It can be used DNA testing, which is a means prevailing legal and biological truth, because every human being is entitled to his true identity.